A randomized phase 3 trial comparing nimotuzumab plus cisplatin chemoradiotherapy versus cisplatin chemoradiotherapy alone in locally advanced head and neck cancer. Issue 18 (31st May 2019) - Patil, Vijay Maruti; Noronha, Vanita; Joshi, Amit; Agarwal, Jaiprakash; Ghosh‐Laskar, Sarbani; Budrukkar, Ashwini; Murthy, Vedang; Gupta, Tejpal; Mahimkar, Manoj; Juvekar, Shashikant; Arya, Supreeta; Mahajan, Abhishek; et al.
Abstract : Background: Because the addition of nimotuzumab to chemoradiation in patients with locally advanced head and neck cancer improved outcomes in a phase 2 study, the authors conducted a phase 3 study to confirm these findings. Methods: This open‐label, investigator‐initiated, phase 3, randomized trial was conducted from 2012 to 2018. Adult patients with locally advanced head and neck cancer who were fit for radical chemoradiation were randomized 1:1 to receive either radical radiotherapy (66‐70 grays) with concurrent weekly cisplatin (30 mg/m 2 ) (CRT) or the same schedule of CRT with weekly nimotuzumab (200 mg) (NCRT).The primary endpoint was progression‐free survival (PFS); key secondary endpoints were disease‐free survival (DFS), duration of locoregional control (LRC), and overall survival (OS). An intent‐to‐treat analysis also was performed. Results: In total, 536 patients were allocated equally to both treatment arms. The median follow‐up was 39.13 months. The addition of nimotuzumab improved PFS (hazard ratio [HR], 0.69; 95% CI, 0.53‐0.89; P = .004), LRC (HR, 0.67; 95% CI, 0.50‐0.89; P = .006), and DFS (HR, 0.71; 95% CI, 0.55‐0.92; P = .008) and had a trend toward improved OS (HR, 0.84; 95% CI, 0.65‐1.08; P = .163). Grade 3 through 5 adverse events were similar between the 2 arms, except for a higher incidence of mucositis in the NCRT arm (66.7% vs 55.8%; P = .01). Conclusions: The addition of nimotuzumab to concurrent weekly CRT improves PFS, LRC, and DFS. This combination provides a novel alternative therapeutic option to a 3‐weekly schedule of 100 mg/m 2 cisplatin in patients with locally advanced head and neck cancer who are treated with radical‐intent CRT. Abstract : The addition of nimotuzumab to concurrent weekly cisplatin and chemoradiotherapy improves outcomes. This combination provides a novel alternative therapeutic option to a 3 weekly schedule of 100 mg/m 2 cisplatin in patients with head and neck cancer.